Shear Strength Characteristics of Sand-Waste Material Mixture - Chow, Shiao Huey; Ismail, Norshida; Abdul Ghani, Abdul Naser (IEM Journal, 2009)
This study investigates the shear strength characteristics of sand-waste material mixtures using direct shear test. Two different waste materials namely tire shred and rubber shred were investigated in this study.